2021
DOI: 10.1016/j.jds.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

High levels of burnout and depression in a population of senior dental students in a school of dentistry in Korea

Abstract: Background/purpose Dental students are exposed to highly stressful environments, making them high-risk for burnout and depression. This study intended to investigate the burnout and depression level in senior dental students in Korea. Materials and methods We conducted a cross-sectional questionnaire study among third- and fourth-year dental students enrolled at Seoul National University. Demographic data, Maslach Burnout Inventory (MBI), Patient Health Questionnaire (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 21 publications
3
50
1
Order By: Relevance
“…As most of the dental stu-35 dents who took part in this study were fully dependent on their families, the negative 36 financial impact could have hampered their academic progress. 37 Low levels of fear were reported amongst dental students in this study. That finding 38 was in contrast to the finding from another study conducted in Bangladesh, which re-39 ported higher levels of fear amongst frontline or essential service workers [5].…”
Section: Levels Of Fearmentioning
confidence: 49%
See 1 more Smart Citation
“…As most of the dental stu-35 dents who took part in this study were fully dependent on their families, the negative 36 financial impact could have hampered their academic progress. 37 Low levels of fear were reported amongst dental students in this study. That finding 38 was in contrast to the finding from another study conducted in Bangladesh, which re-39 ported higher levels of fear amongst frontline or essential service workers [5].…”
Section: Levels Of Fearmentioning
confidence: 49%
“…Moreover, prior evidence indicated that dental education used to 24 generate more stress and burnout than medical educations [36]. Due to more interactive 25 involvement with patient during theoretical and clinical courses [37]. In this study, 3rd 26 year clinical students were more prone to have psychological distress due to COVID-19.…”
Section: Levels Of Fearmentioning
confidence: 66%
“…This might be due to increased risk of exposure of COVID-19 among dental students. Moreover, prior evidence indicated that dental education generated more stress and burnout than medical educations [ 38 ], due to more interactive involvement with patients during theoretical and clinical courses [ 39 ]. In this study, third year clinical students were more prone to having psychological distress due to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, medical and dental schooling is perceived as a highly stressful education, where students face a higher level of stress, anxiety, and depression compared to peers studying other subjects [ 9 , 10 , 11 ]. In particular, research shows that dental students are prone to higher burnouts compared to medical students as it involves patient interaction during both theoretical and clinical course elements [ 12 ]. Obtaining an undergraduate academic degree in dentistry requires tedious education and demands to acquire deep knowledge on the field.…”
Section: Introductionmentioning
confidence: 99%